(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Now a day in India Fin Tech plays an important role for financial inclusion with the entrance of various new entities like small finance banks and payment banks. Where there is a technology adopted by niche banks which is contributing to digitalization for financial inclusion. As we all know that Fin Tech helps to achieve financial inclusion as well as it lines up the efficiency in operations, cost minimization at a faster pace.